2019
DOI: 10.1111/coa.13454
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of pre‐treatment serum albumin in patients with nasopharyngeal carcinoma: A meta‐analysis and systematic review

Abstract: Background Pre‐treatment serum albumin (ALB) is a novel index that was identified in recent years and is considered to be closely related to the prognosis of nasopharyngeal carcinoma (NPC). However, the association between ALB and NPC remains controversial. Objective of Review To assess the prognostic significance of pre‐treatment serum ALB in patients with NPC. Type of Review A systematic review and meta‐analysis. Search Strategy We searched PubMed, the Cochrane Library and the Web of Science for studies publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
(65 reference statements)
5
23
0
Order By: Relevance
“…[50][51][52] Moreover, ALB is known as a common nutritional index marker and acts as a valuable prognostic indicator in NPC. 38,47 Our study confirmed that a decreased level of pre-treatment ALB implies a poor EM-DMFS in NPC. Furthermore, our results indicate that the female sex is a favorable prognostic factor for EM-DMFS in NPC, confirming previous studies.…”
Section: Discussionsupporting
confidence: 78%
“…[50][51][52] Moreover, ALB is known as a common nutritional index marker and acts as a valuable prognostic indicator in NPC. 38,47 Our study confirmed that a decreased level of pre-treatment ALB implies a poor EM-DMFS in NPC. Furthermore, our results indicate that the female sex is a favorable prognostic factor for EM-DMFS in NPC, confirming previous studies.…”
Section: Discussionsupporting
confidence: 78%
“…Some studies indicated that decreased HGB is significantly related to poorer prognosis in patients with NPC ( 26 , 27 ). ALB is also an important indicator reflecting the patients’ nutritional status and has been used for prognostic assessment of patients with NPC ( 28 ). CRP, an acute-phase protein, increases quickly related to inflammation or infection ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Low level of PNI, AAPR, AGR, and ALB had been reported to be associated with poor survival in NPC, however, the combined analysis has not been reported (16,19,(23)(24)(25)(26). Moreover, the studies on the effect of serum biochemical indexes on toxicity with radiotherapy and the prognostic value of SIS, BUN, and CREA for NPC have not yet been reported.…”
Section: Introductionmentioning
confidence: 97%